Design and Verification of Calorimeter for CFETR Neutral Beam Injection System Prototype with Negative Ion Source. (18th August 2022) - Tao, Ling; Xie, Yuanlai; Hu, Chundong; Xu, Yongjian; Yi, Wei; Tang, Ning
Abstract: Currently, a neutral beam injection (NBI) system prototype with a 200-keV negative ion source, called the negative neutral beam injection (NNBI) system, is under construction for the China Fusion Engineering Test Reactor Project. In the NNBI system, the calorimeter is an extremely important high-heat-flux component, and its panels have to withstand a heat flux density of up to dozens of MW/m 2 under some extreme conditions; thus, its efficient heat transfer enhancement design and the corresponding supporting structural design are most important, especially under the condition of a 3600-s long pulse. According to the detailed design requirements of the NNBI system, an overall design scheme of the calorimeter based on the heat transfer enhancement structure of the swirl tube (SW for short) is proposed in this paper. By using the gas-liquid two-phase flow boiling model and the supporting structure's finite element model, the heat transfer performance of the heat exchange module, the mass flow distribution and pressure drop of the entire cooling circuit of the component, and the strength of the support structure are evaluated to verify the feasibility of the design scheme. Finally, based on the proposed design scheme, the detailed design of the temperature monitor system, which has high reliability and economy, is completed. This research provides important theoretical and engineering support for the structural development of the calorimeter for the NNBI verification prototype and will also provide references for the design and development of other internal components of large-scale fusion devices.